2010
DOI: 10.1177/112067211002000612
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Short-Duration Topical Treatment with Azithromycin Oil-Based Eyedrops in an Experimental Model of Corneal Refractive Surgery

Abstract: Topical administration of T1225 oil-based azithromycin eyedrops was well tolerated in both unmanipulated hen corneas and those treated with corneal refractive surgery (PRK and LASIK). T1225 demonstrated a potent antibiotic effect after LASIK treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…29 In this study, different from its immunomodulatory effect, we investigated whether topically used AZM also possesses antiapoptotic effect on corneal epithelial and endothelial cells, as a decrease in corneal stromal apoptosis with the administration of topical AZM has been previously reported in an experimental model of refractive surgery. 30 In this study, we determined that the number of TUNEL+ cells in the corneal epithelium of rats with alkali burn was significantly decreased with the topical application of AZM. Moreover, we found that topical AZM was capable of reducing the TNF-a density increased in the corneal epithelium as a result of alkali burn.…”
Section: Discussionmentioning
confidence: 99%
“…29 In this study, different from its immunomodulatory effect, we investigated whether topically used AZM also possesses antiapoptotic effect on corneal epithelial and endothelial cells, as a decrease in corneal stromal apoptosis with the administration of topical AZM has been previously reported in an experimental model of refractive surgery. 30 In this study, we determined that the number of TUNEL+ cells in the corneal epithelium of rats with alkali burn was significantly decreased with the topical application of AZM. Moreover, we found that topical AZM was capable of reducing the TNF-a density increased in the corneal epithelium as a result of alkali burn.…”
Section: Discussionmentioning
confidence: 99%
“…After intraperitoneal and topical anesthesia, corneal lesions were performed on both eyes of 40 mice by laser induced photorefractive keratectomy (PRK) [ 19 ]. To induce the epithelial and stromal laser lesion, each eye was placed under a Wavelight Allegretto Wave PR-020407 excimer laser (Wavelight GmbH, Alcon, Erlangen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…All animals were treated with topical eye drops of azythromycin 1.5% (Azyter, Laboratoires Thea, Clemrmont-Ferrand, France) for antimicrobial prophylaxis two times daily for three days after lesion [ 19 ]. Eighty eyes of 40 mice were divided in four treatment groups ( n = 20 eyes per group), which included control, stem cells, basic serum, and plasma rich in growth factor (PGRF).…”
Section: Methodsmentioning
confidence: 99%
“…La cirugía se realizó como se describió previamente 8,21,[37][38][39][40][41][42][43] . Los 2 ojos de cada ratón fueron tratados mediante cirugía PRK (photorefractive keratectomy) con una zona de ablación de 2,0 mm en la córnea central y 45 m de profundidad (incluyendo el epitelio) con un láser excímero VISX Star S2 (Abbott Medical Optics Inc.…”
Section: Inducción De La Lesión Corneal Mediante Cirugía Fotorrefractivaunclassified